2008
DOI: 10.1080/13506120802524684
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin forms amyloid fibrils at physiological pH with ultrasonication

Abstract: In transthyretin (TTR)-related amyloidosis, wild-type TTR (WT-TTR), as well as mutated TTRs play important roles in the pathogenesis of senile systemic amyloidosis and familial amyloidotic polyneuropathy. However, WT-TTR usually forms stable tetramers at physiological pH, and the mechanism of such fibril formation under physiological conditions remains to be elucidated. In this study, we demonstrated WT-TTR amyloid fibril formation at physiological pH with ultrasonication. Cross-linked SDS-PAGE and circular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…CD accordingly revealed a considerably rearranged structure of protofibrils compared to native TTR ( Fig. 8B ), as also observed using different fibrillation protocols 24 51 80 . The TTR crystal structure contains 5% α-helix, 48% β-sheet and 47% turns and disordered components.…”
Section: Figuresupporting
confidence: 74%
“…CD accordingly revealed a considerably rearranged structure of protofibrils compared to native TTR ( Fig. 8B ), as also observed using different fibrillation protocols 24 51 80 . The TTR crystal structure contains 5% α-helix, 48% β-sheet and 47% turns and disordered components.…”
Section: Figuresupporting
confidence: 74%
“…The propensity of TTR under mildly acidic conditions (pH 3.5 to 5) to adopt aggregation has been reviewed in detail. , In spite of an acidic pH, the importance of an aggregation-prone unfolded state that emerges through various denaturing conditions has been emphasized as well. For instance, TTR conformational changes favoring the aggregation under chemical, high pressure, and thermal denaturation, , and also ultrasonication have been reported. Accordingly, we have characterized two distinct aggregation pathways for mTTR, taking advantage of various biophysical assays.…”
Section: Resultsmentioning
confidence: 99%
“…Stathopulos et al 34) showed that ultrasonication results in the formation of amyloid-like aggregates. Subsequently, amyloid fibrillation of various proteins such as -synuclein, 52) 2-m, 53) transthyretin, 54) and mouse prion proteins 50) was reported to be accelerated by ultrasonic irradiation. Under certain conditions, aggregation of amyloid peptide is also promoted by ultrasonication.…”
Section: Mechanism Of Ultrasonication-triggered Fibrillation and Futumentioning
confidence: 99%